Interpretation of Mykola Khvylovyi's fiction on the stage of contemporary Ukrainian theatre - ПИЛИПЕЙ, Олена; КОЗАКОВА, Лідія (Видавничо-поліграфічний центр “Київський університет”, 2025)
The article offers an overview of contemporary theatrical productions based on the works of Mykola Khvylovyi and attempts to explain the relevance of theatrical interpretations of this author's texts, given that Khvylovyi was a prose writer who never created dramatic works. It analyzes the inherent theatricality of his prose as well as the directors' interpretations of individual stage productions inspired by Khvylovyi's works. The article traces how theatrical performances contribute to the popularization of the writer's legacy in the contemporary world, emphasizing the importance of shaping and rethinking national identity through the means of theatrical art.

У статті йдеться про огляд сучасних театральних постановок за мотивами творів М. Хвильового, здійснено спробу пояснити актуальність саме театральної інтерпретації творів цього автора, адже М. Хвильовий - прозаїк, який ніколи не писав драматичних творів. Проаналізовано сценічність прози автора, режисерське прочитання кожної з вистав за мотивами творів М. Хвильового. У статті простежено, як театральні перфоманси сприяють популяризації творчості письменника в сучасному світі, наголошуючи на важливості формування і переосмислення національної ідентичності засобами театрального мистецтва.
Інтерпретація художньої прози Миколи Хвильового на сцені сучасного українського театру
Keywords: theatre; interpretation; theatrical production; director's concept; national identity; thriller; spiritual disorientation; stage potential; musical; performance; etc.; театр; інтерпретація театральна постановка; режисерська концепція; національна ідентичність; трилер; душевний блуд; сценічний потенціал; мюзикл; вистава тощо